Molecular investigation of effects of probiotic on papG and iutA genes in different strains of E.coli isolated from urinary tract infection - Romina Rezaei; Mona Mohammad Aliha; Roudabeh Behzadi Andouhjerdi; Maryam Tajabadi Ebrahimi (Archive of Urological Research - Peertechz Publications, 2023)
Escherichia coli-induced urinary tract infections (E.coli-UTIs) are considered one of the most prevalent infections in Iran. One of the important factors of pathogenicity, particularly in its binding to epithelial cells, is the presence of iutA and papG virulence genes in Escherichia coli (E.coli). Lactobacilli, as a group of probiotics, play a vital role in the body and are useful in some cases due to their therapeutic effects. The aim of this study was to evaluate how the molecular activity of Lactobacillus casei PTCC1608 influences different strains of pathogenic E.coli isolated from urinary infections through PCR. In this study, the pathogenic strain of E.coli was isolated from the patients with Urinary Tract Infections (UTIs) and analyzed by the use of the PCR method. Then, the strains with positive genotypes were isolated and the antimicrobial effect of Lactobacillus casei was evaluated through the disc diffusion and dilution methods in liquid medium. The antimicrobial effect of Lactobacillus casei on E.coli bacteria isolated from urine samples from 40 patients with UTI was studied. In addition, the results of the antibiotic sensitivity test at 1:10 dilution showed a growth inhibition zone of 9 mm. The results indicated that the isolated bacterium was not resistant to the ampicillin and the antibiotic treatment was effective for this strain. Moreover, the probiotic also plays a therapeutic role and can improve urinary infections.